Principal Assignments in Limbo: A Qualitative Study on the Processes and Potential Outcomes of the Recent Principal Assignment Initiative in Turkey - Mahmut Kalman; M. Semih Summak; Ismail Cimen (ÜNİVERSİTEPARK Limited, 2017)
This study aimed at investigating school principals' and teachers' perceptions of the processes pursued in principal assignments and the potential outcomes of the recently enacted initiative concerning the assignments in Turkish public schools. The intrinsic case study was used as the research design. The data were collected through one-on-one interviews and focus group discussions. It was concluded that the processes, practices, and procedures followed in the recent initiative were not considered procedurally just and ethical by principals and teachers, and that deservingness had nearly no role in the principal assignments. The participants' thoughts and perceptions overall implied that the principal assignments were entrenched in a quagmire of personal contacts and politics. More important, outcome favorability did not seem to have affected the perceptions of most of the principals. However, there were no significantly divergent views amongst the principals and teachers in terms of justifying and evaluating the initiative.